2020
DOI: 10.1177/2192568220966328
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Zones on MRI of the Cervical Spine in Patients: Epidemiology and Association With Pain and Disability

Abstract: Study Design: Retrospective cohort study. Objectives: This study aimed to address the prevalence, distribution, and clinical significance of cervical high-intensity zones (HIZs) on magnetic resonance imaging (MRI) with respect to pain and other patient-reported outcomes in the setting of patients that will undergo an anterior cervical discectomy and fusion (ACDF) procedure. Methods: A retrospective cohort study of ACDF patients surgically treated at a single center from 2008 to 2015. Based on preoperative MRI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…These results were different from the results of Tsuji et al [ 15 ] study, who found that of Modic changes affected 47 intervertebral disc levels (3.48%) in all 1158 cervical intervertebral levels. The study conducted by Nguyen demonstrated that 58 patients (6.7%) within the 861 patients were found HIZs in their cervical spine [ 16 ]. The patients in our cohort with only mild to moderate cervical spine dysfunction symptoms were the likely cause of this difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were different from the results of Tsuji et al [ 15 ] study, who found that of Modic changes affected 47 intervertebral disc levels (3.48%) in all 1158 cervical intervertebral levels. The study conducted by Nguyen demonstrated that 58 patients (6.7%) within the 861 patients were found HIZs in their cervical spine [ 16 ]. The patients in our cohort with only mild to moderate cervical spine dysfunction symptoms were the likely cause of this difference.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Chen et al [12] used the Miyazaki grades to demonstrate that cigarette smoking could accelerate the process of CDD, leading to more severe neckshoulder pain. The relationship between MRI findings on cervical spine and factors influencing CDD has been documented extensively [13][14][15][16][17]. Some studies demonstrated that CDD on MRI was observed in the asymptomatic subjects [18] [1-3] [1-3] [ [1][2][3].…”
Section: Introductionmentioning
confidence: 99%